'Pinholes in my arms': the vicious cycle of vascular access. (22nd July 2021) - Kelly, Linda J; Snowden, Austyn
Abstract : Background: Vascular access devices (VADs) are essential for delivery of intravenous therapies. There are notable gaps in the literature regarding a focus on patient experience and meaning-making related to living with a VAD, specifically a central venous access device (CVAD). Aims: To explore how patients make sense of living with a CVAD. Methods: This study followed an interpretive phenomenological analysis (IPA) approach. Purposive sampling was used to identify 11 cancer patients who had a CVAD in situ. One-to-one semi-structured interviews were performed. Interviews were digitally recorded, transcribed and analysed by the lead author. Findings: Four superordinate themes were identified: the self under attack; being rescued/being robbed; protection of others/protection of self; bewilderment and dismay at lack of staff competence. Conclusion: Having a CVAD affects the psychological, social, and personal self and impacts on self-esteem and self-image. Despite this, CVADs are accepted by patients and are eventually 'embodied' by them.